Pendidikan Nilai Dan Pembanguan Warganegara Menerusi Pendekatan Pengajaran Di Bilik Darjah - Jusoh, Ismail (Penerbit Universiti Sains Malaysia, 1994)
This paper is about the concepts of values and values education and the relationship between values education and citizenship development. The first part of the paper discusses the concept of values as perceived by some writers. The second part discusses some of the findings based on a survey conducted to elucidate the understanding of the concept by some student teachers. This excercise was performed by asking the students words that they used to define values or any other words which were associated with values. Comparison between male and female perception of values was computed. Finally a model to inculcate values through classroom teaching is presented.